2016
DOI: 10.1179/1743281215y.0000000040
|View full text |Cite
|
Sign up to set email alerts
|

Influence of charcoal replacing coke on microstructure and reduction properties of iron ore sinter

Abstract: This study was carried out to determine the influence of using charcoal as a supplementary fuel on the microstructure and reduction properties of sinter. The primary fuel was coke breeze with 0, 20, 30 and 40% replacement of weight input with charcoal to produce sinter. Experimental results indicate that when the replacement percentage of charcoal to coke breeze increased from 0 to 40%, the porosity and FeO content of sinter also rose. These changes result in an enhancement from 79.8 to 84.3% for the reducibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…The temperatures correspond also with the development of magnetite, which as a carrier of FeO has better conditions for formation at higher temperatures. This development could suggest slightly lower reducibility of sinters with alternative fuels; on the other hand, it could be compensated by higher amount of voids and pores remaining after burned biomass, ergo higher reaction surface of sinter [6]. All this applies to the sample O13, where there is a decrease in all three phases -Fe 3 O 4 , SFCA, and SFCA-I.…”
Section: The Development Of Phase Composition At Fuel Substitutionmentioning
confidence: 98%
See 1 more Smart Citation
“…The temperatures correspond also with the development of magnetite, which as a carrier of FeO has better conditions for formation at higher temperatures. This development could suggest slightly lower reducibility of sinters with alternative fuels; on the other hand, it could be compensated by higher amount of voids and pores remaining after burned biomass, ergo higher reaction surface of sinter [6]. All this applies to the sample O13, where there is a decrease in all three phases -Fe 3 O 4 , SFCA, and SFCA-I.…”
Section: The Development Of Phase Composition At Fuel Substitutionmentioning
confidence: 98%
“…Sect. (1) B (2018) 9 -20 partial substitution of coke breeze by charcoal evaluated by tumbler index decreases as the alternative fuel ratio increases; therefore, the fuel substitution ratio is limited, mostly to 40% on the mass or fixed carbon basis [6][7][8]. The use of biomass in raw state has been proven disadvantageous due to the high moisture content and low calorific value [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The authors were unable to find any research related to any kind of biomass utilization in chromite pellet sintering. Still a vast body of studies were found concerning biomass − such as charcoal − utilization in iron ore sintering . These studies indicate that 100% substitution of coke with charcoal is not possible, if the same tumble strength and reduction disintegration of the agglomerate is required.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of charcoal substitution on the performance of the iron ore sintering process itself (yield, productivity, combustion behavior, thermal profile of sinter bed, sintering speed etc.) has been evaluated in earlier studies . Charcoal use in chromite concentrate sintering has been investigated in the work of Rocha et al The findings of these studies give basis to investigate the impact of coke substitution with charcoal in chromite pellet sintering.…”
Section: Introductionmentioning
confidence: 99%
“…Our 2 Advances in Materials Science and Engineering group also did a lot of work on the influences of biochar replacing coke breeze on sintering process. The research showed that it could reduce emissions of NOx, SOx, and so on when applying the carbonized products of straw, trees, and molded-sawdust [18][19][20][21]. There were lots of differences between biochar and conventional fuels in terms of chemical composition, physical properties, proximate analysis, and so on.…”
Section: Introductionmentioning
confidence: 99%